B lymphocytes transdifferentiate into immunosuppressive erythroblast-like cells - Yang, Zhe; Wang, Zheng; Wu, Lei; Wang, Ying; Xu, Zhihui; Liu, Ying; Wang, Fangfang; Yu, Duonan (Frontiers in Immunology, 2023)
Recent studies have demonstrated that a particular group of nucleated cells that exhibit erythroid markers (TER119 in mice and CD235a in humans) possess the ability to suppress the immune system and promote tumor growth. These cells are known as CD45+ erythroid progenitor cells (EPCs). According to our study, it appears that a subset of these CD45+ EPCs originate from B lymphocytes. Under conditions of hypoxia, mouse B lymphoma cells are capable of converting to erythroblast-like cells, which display phenotypes of CD45+TER119+ cells, including immunosuppressive effects on CD8 T cells. Furthermore, non-neoplastic B cells have similar differentiation abilities and exert the same immunosuppressive effect under anemia or tumor conditions in mice. Similar B cells exist in neonatal mice, which provides an explanation for the potential origin of immunosuppressive erythroid cells in newborns. Additionally, CD19+CD235a+ double-positive cells can be identified in the peripheral blood of patients with chronic lymphocytic leukemia. These findings indicate that some CD45+ EPCs are transdifferentiated from a selective population of CD19+ B lymphocytes in response to environmental stresses, highlighting the plasticity of B lymphocytes. We anticipate a potential therapeutic implication, in that targeting a specific set of B cells instead of erythroid cells should be expected to restore adaptive immunity and delay cancer progression.